At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Answer:
x = -6
y = -16
Step-by-step explanation:
if you subtract the two equations from each other then the 'y' terms will be eliminated:
2x = -12
x = -6
solve for 'y':
4(-6) - 3y = 24
-24 - 3y = 24
-3y = 48
y = -16
6x-3y=12
4x-3y=24
2x=-12
x=-6
6(-6)-3y=12
-36-3y=12
-3y=48
y=-16
Answer: x=-6, y=-16
(sorry if im wrong)
4x-3y=24
2x=-12
x=-6
6(-6)-3y=12
-36-3y=12
-3y=48
y=-16
Answer: x=-6, y=-16
(sorry if im wrong)
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.